Elevating services: Services trade policy, WTO commitments, and their role in economic development and trade integration - Martin Roy (World Trade Organization (WTO), 2019)
Services have long been perceived as playing a secondary role in world trade. In particular, the role of services trade policies and multilateral services commitments often tends to be downplayed. However, in value added terms, services account for about 50% of world trade and are significant in exports of countries of all levels of development. In addition, cross-border trade is expanding as a result of technological advances, and the supply of services by foreign affiliates (mode 3) exceeds trade through other modes of supply. Services trade policies, which cover a wide range of "inside-the-border" measures, are an important determinant of foreign direct investment, economy-wide productivity, manufacturing competitiveness and exports, and flows of services value added. This paper underscores, on the basis of recent services data and a growing body of research on the impact of services policies, the role of services trade in economic development, trade integration, and inclusiveness. It argues that the limited attention given to services trade policies and to international commitments is increasingly out of step with the role of services in the global economy. Indeed, services trade policies are often restrictive and multinational commitments are generally modest. Taking steps to raise the profile of services trade within government policy-making would help close this gap and highlight the contribution of services trade policy to a wide range of broader national objectives that have an important services dimension, whether SME and gender policy, or the achievement of Sustainable Development Goals (SDGs).
Keywords: F13; F15; F53; L8; 330; WTO; GATS; trade in services; trade in value added